KUALITAS PELAYANAN HAJI DI KEMENTERIAN AGAMA KABUPATEN GRESIK - Habibah, Jessica Wildani; Arundinasari, Indira (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2024)
Indonesia's population is predominantly Muslim. The desire to perform the fifth pillar of Islam, the Hajj, is very high. Given the many people who want to go on Hajj, of course, the Indonesian government is expected to be able to provide good public services so that pilgrims can comfortably carry out their worship. Public services cannot be separated from the life of the state, with good public services that will certainly determine the image or quality of a government agency or company. The Ministry of Religion of Gresik Regency, which is the organizer of Hajj and Umrah in Gresik Regency, where the pilgrims in Gresik Regency are ranked 3rd (third) largest contributor in East Java. With so many pilgrims in the Gresik district, it is certainly a challenge for the field of organizing Hajj and Umrah in the Gresik district regarding the quality of services provided. This study aims to determine how the quality of Hajj services at the Ministry of Religion of Gresik Regency. Researchers used a qualitative method of descriptive analysis using the theory of Pasuraman and Zeithmal with 5 dimensions namely Reliability, Responsiveness, Assurance, Empathy, and Tangibles. Data collection is done by conducting interviews, observations, and literature studies. The results of the research that have been assessed from 5 (five) dimensions of Pasuraman and Zeithmal's theory which show the results at the Ministry of Religion of the Gresik Regency are still not good in the dimensions of tangibles and responsiveness. Keywords: Hajj; Quality; Service; Public